Comparison of diagnostic techniques to measure damage growth in a stiffened composite panel. (October 2020) - Clay, Stephen; Brown, Kevin; Jenkins, Caitlin; Hall, Melissa; Knoth, Philip; Smyers, Brian
Abstract: A research study was performed during which a hat-stiffened composite panel was manufactured and tested in order to assess the abilities of four advanced diagnostic tools to characterize skin-to-stringer separation growth in post-buckled conditions. Teflon film was inserted between the hat flanges and the skin to create an initially disbonded region. The four diagnostic tools included a hand-held ultrasonic scanner, 3D digital image correlation, a fiber optic strain interrogator, and thermo-elastic stress analysis. A standard procedure was used for the ultrasonic system, but the other three advanced devices required MATLAB algorithms to define the damage zone based on peak strains along the loading direction. The results showed that all four techniques were able to characterize skin-to-stringer separation, with the largest difference between the measurements being approximately 5%.